Understanding of Women Empowerment and Socio- economic Development: A Conceptual Analysis. (Patan Pragya, 2022)
Empowerment is defined as the authority or power that given to someone to do something. Women empowerment is the strategies of women to increase their control of resources and generate decision making capacity. Socio-economic development is the process of social and economic development in a society. Women are the essential part of our society and half of the total population, the sustainable development of a country depends on the maximum utilization and equal participation of both women and men. Development of a nation could only be achieved if women are empowered, and their social and economic status is improved; it is possible only by adopting definite social and economic policies with a view of total development of women. The purpose of this paper is to understand women empowerment and socio-economic development conceptually. This paper is descriptive and qualitative and based on secondary data.